Kontribusi Minat Belajar Dan Kompetensi Kepribadian Guru Terhadap Hasil Belajar Pada Mata Diklat Seni Grafis Jurusan Multimedia di SMK Negeri 1 Kecamatan Luak - Isranika Bukharla; Zulkifli Naansah; Putra Jaya (Universitas Negeri Padang, 2014)
This study aimed to determine the contribution of learning interest and personal competence of teachers toward student’s grade for Graphic Arts subject at X class of Multimedia Department at SMK Negeri 1 Kecamatan Luak. The type of this research is a descriptive correlational. Population in this research are 65 students, and samples are amount to 39 students. Samples are taken by simple random sampling technique. Student’s grade data obtained from teacher’s of graphic arts at SMK Negeri 1 Kecamatan Luak. And data of learning interest and personal competence of teachers were collected through a questionnaire using a Likert scale that has been tested for validity and reliability. The results of data analysis showed: (1) Learning interest and personal competence of teachers together contributed 61.5% for student’s grade, (2) Learning interest contributed 17.14% for student’s grade, (3) Competence teacher's personality contributed 16.64% for student’s grade. This research suggest that student’s interest in learning and personal competence of teachers give contribution to student’s grade.